2019
DOI: 10.1017/wet.2019.76
|View full text |Cite
|
Sign up to set email alerts
|

Bermudagrass tolerance of indaziflam PRE applications in forage production

Abstract: Bermudagrass is a major forage species throughout Georgia and the Southeast. An essential part of achieving high-yielding, top-quality forages is proper weed control. Indaziflam is a residual herbicide that controls many broadleaf and grass species by inhibiting cellulose biosynthesis. Research conducted in Tift and Colquitt counties in Georgia determined optimal PRE rates for indaziflam for bermudagrass forage production. Treatments applied at spring greenup of established ‘Alicia’ bermudagrass included indaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
(19 reference statements)
1
10
0
Order By: Relevance
“… Ekeleme et al (2020) obtained similar results in another study in Oyo State in Nigeria and attributed the delay in sprouting to indaziflam, which suppressed buds exposed to the herbicide. Nicholas et al (2019) reported that indaziflam at 155 and 234 g ha −1 caused transient stunting of Bermuda grass at 44 days after planting. Indaziflam is a nonselective cellulose-inhibiting herbicide that affects cell elongation and the growing meristematic regions ( Brabham et al, 2014 ; Edwards et al, 2015 ; Neal, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“… Ekeleme et al (2020) obtained similar results in another study in Oyo State in Nigeria and attributed the delay in sprouting to indaziflam, which suppressed buds exposed to the herbicide. Nicholas et al (2019) reported that indaziflam at 155 and 234 g ha −1 caused transient stunting of Bermuda grass at 44 days after planting. Indaziflam is a nonselective cellulose-inhibiting herbicide that affects cell elongation and the growing meristematic regions ( Brabham et al, 2014 ; Edwards et al, 2015 ; Neal, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Blackberry primocanes and floricanes exhibited no visual injury to any herbicide treatment (data not shown). As previously noted, there are many reports of little to no visual injury for indaziflam applied to perennial crops (Basinger et al 2019;González-Delgado et al 2017;Grey et al 2018Grey et al , 2016Hurdle et al 2019).…”
Section: Blackberrymentioning
confidence: 88%
“…This was always transient and no longer noted 8 wk after treatment. Many reports of little to no visual injury have been made for indaziflam applied to perennial crops (Basinger et al 2019;González-Delgado et al 2017;Grey et al 2018Grey et al , 2016Hurdle et al 2019).…”
Section: Blueberrymentioning
confidence: 99%
See 2 more Smart Citations